The noise-induced harmful effect assessment based on the properties of the human hearing system - KOTUS, Józef; KOSTEK, Bożena (Archives of Acoustics, 2008)
In this paper a new method of assessing noise-induced harmful effects on the human hearing system is described. The method proposed determines the cumulative impact on hearing system produced by the excessive noise taking into consideration properties of the human hearing system. Based on the predicted effects of the noise exposure, the new types of noise indicators are engineered. The evaluation of these indicators employed various types of noise. The indicators proposed can improve assessment of the harmful effect caused by the noise exposure. An influence of the type of the critical band representation of the hearing system (Bark or ERB scales) on the noise indicator effectivness is also discussed.